Long‐term effects of land‐use change on bird communities depend on spatial scale and land‐use type. Issue 11 (22nd November 2019) - Allen, Daniel C.; Bateman, Heather L.; Warren, Paige S.; de Albuquerque, Fabio Suzart; Arnett‐Romero, Sky; Harding, Bridget
Abstract: Land‐use transformation is one of the most important and pervasive ecological changes occurring across the Earth, but its long‐term effects are poorly understood. Here, we analyze the effects of urban and agriculture development on bird biodiversity and community structure over a 16‐yr study period. We found that long‐term effects of land‐use change are dependent on spatial scale and land‐use type. At the regional scale, we found that gamma diversity (total number of species observed) declined by 10% over time. At the landscape spatial scale, we found that beta diversity (uniqueness of bird communities) increased by 16% over time. Additionally, the average contributions of urban riparian bird communities to beta diversity were generally the highest but declined by 26% over the study period. Contributions of urban communities to beta diversity were generally the lowest but increased by 10% over time. At the local scale, we observed different responses for different measures of alpha diversity. For bird species richness, temporal changes varied by land use. Species richness declined 16% at sites in desert riparian areas but increased by 21% and 12% at sites in urban and agricultural areas, respectively. Species evenness declined across all land uses, with some land uses experiencing more rapid declines than others. Our analysis of species groups that shared certain traits suggests that these community‐level changes were driven by species that are small, breed onsite, and feed on insects, grains, and nectar. Collectively, our results suggest that biodiversity declines associated with land‐use change predominate at the regional and local spatial scale, and that these effects can strengthen or weaken over time. However, these changes counterintuitively led to increases in biodiversity at the landscape scale, as bird communities became more unique. This has implications for conservation and management as it shows that the effects of land‐use modification on biodiversity may be positive or negative depending on the spatial scale considered.